2018
DOI: 10.1038/s41398-017-0073-7
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of bipolar depression with minocycline and/or aspirin: an adaptive, 2×2 double-blind, randomized, placebo-controlled, phase IIA clinical trial

Abstract: Given evidence of chronic inflammation in bipolar disorder (BD), we tested the efficacy of aspirin and minocycline as augmentation therapy for bipolar depression. Ninety-nine depressed outpatients with BD were enrolled in a 6 week, double-blind, placebo-controlled trial, and randomized to one of four groups: active minocycline (100 mg b.i.d.) + active aspirin (81 mg b.i.d.) (M + A); active minocycline + placebo aspirin (M + P); placebo-minocycline + active aspirin (A + P); and placebo-minocycline + placebo asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(90 citation statements)
references
References 29 publications
1
88
1
Order By: Relevance
“…The inhibition of COX‐1 is neuroprotective based on preclinical evidence while COX‐2 inhibition increases leukocyte recruitment into the brain exacerbating tissue damage . A pilot randomized trial suggests that aspirin might impact bipolar depression …”
Section: Introductionmentioning
confidence: 99%
“…The inhibition of COX‐1 is neuroprotective based on preclinical evidence while COX‐2 inhibition increases leukocyte recruitment into the brain exacerbating tissue damage . A pilot randomized trial suggests that aspirin might impact bipolar depression …”
Section: Introductionmentioning
confidence: 99%
“…They are responsible for the production of cytokines and chemokines, referred to as innate immunity. They are located in the microglia, thyroid gland, adrenal gland, intestines and for a certain developmental period in the thymus gland [13]. At this point, it is important to remember that the first term designating mood stabilizing agents was thymoleptics.…”
Section: Discussionmentioning
confidence: 99%
“…Any suggestion that the present study missed microglial activation because PET TSPO binding does not detect it or that minocycline is ineffective against it would be premature in the light of recent studies in depression. Two studies 76,77 reported increased PET TSPO binding in patients with major depressive disorder, and a further two studies 78,79 reported that minocycline substantially reduced depression in treatment-resistant patients 78 and in a sample of patients with bipolar depression. 79 This suggests that fundamental differences may exist between the immune basis of psychosis and that of depression.…”
Section: Mechanistic Markersmentioning
confidence: 99%